If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 9i = 10 + -3yi Reorder the terms: 9i + 5x = 10 + -3yi Solving 9i + 5x = 10 + -3iy Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '3iy' to each side of the equation. 9i + 3iy + 5x = 10 + -3iy + 3iy Combine like terms: -3iy + 3iy = 0 9i + 3iy + 5x = 10 + 0 9i + 3iy + 5x = 10 Add '-5x' to each side of the equation. 9i + 3iy + 5x + -5x = 10 + -5x Combine like terms: 5x + -5x = 0 9i + 3iy + 0 = 10 + -5x 9i + 3iy = 10 + -5x Reorder the terms: -10 + 9i + 3iy + 5x = 10 + -5x + -10 + 5x Reorder the terms: -10 + 9i + 3iy + 5x = 10 + -10 + -5x + 5x Combine like terms: 10 + -10 = 0 -10 + 9i + 3iy + 5x = 0 + -5x + 5x -10 + 9i + 3iy + 5x = -5x + 5x Combine like terms: -5x + 5x = 0 -10 + 9i + 3iy + 5x = 0 The solution to this equation could not be determined.
| 2x+9+9x-8=8x+19 | | 15x-3(6+5x)=-18 | | x*x=16+(x+-4)(x+2) | | 8+6y=7y | | 2x+6=-6-2 | | -4(v+7)=-(1+7v) | | 14.3=-1.4-3d | | x*x=16+(x-4)*(x+4) | | P/g=10 | | 9x-5-6x-2=6x-1 | | -10-9z+10z=-12 | | 5g+2=10-3g-8 | | -5r+5=-6r+2 | | (3x-1)(6x+9)=0 | | (x-4)*(x+4)=486 | | 3.50t+5.50+6t=51 | | d+6=10-3d | | 1-7n-1=-8n | | (x-4)*(x-4)=486 | | 60+60+x-20=360 | | 9x-5-6x-2=6x-7 | | -4n+6n=6n-12 | | 2q-6=3+3q | | 60+60+x-20=90 | | 2(x-2)(x-6)=0 | | 17/3x1/3 | | -x-2=12+x | | 60+60+x-20=180 | | 2g=g+10 | | 12/2q=36 | | 3y=x+8.5 | | 5=x-3(x+2) |